Development and delivery of pharmacy services for the London 2012 Olympic and Paralympic Games. Issue 1 (20th December 2012) - Stuart, Mark; Mottram, David; Erskine, David; Simbler, Stephen; Thomas, Trudy
Abstract : The London Organising Committee for the Olympic and Paralympic Games was established to plan and deliver the London 2012 Games. Within the Medical Services network, the Pharmacy Planning Committee (PPC) developed and delivered pharmacy services that were among the most advanced and comprehensive of any Games. The PPC designed a pharmacy service according to UK standards, operated through three polyclinics at the Athlete Villages. From these polyclinic pharmacies a system was set up for the supply, storage and management of medicines for use at all competition and training venues. To ensure safe and standardised approaches were used, a comprehensive set of policies and standard operating procedures was developed. Pharmacy guides, including drug formularies, were provided for the medical prescribers both within the polyclinics and as members of the Olympic and Paralympic Teams visiting the Games from around the world. Over 100 pharmacists and pharmacy technicians were recruited as the volunteer workforce for the Games. A training and education programme was developed to prepare this team to work in the unique environment of an Athlete Village polyclinic. A total of 5200 prescriptions (6849 items) were dispensed through the polyclinic pharmacies over the period of the Games. In addition, a Pharmacy Minor Ailments Scheme for non-athletes was introduced for the first time at an Olympics, with 1046 encounters taking place over the period of the Games. Valuable lessons were learnt from developing and delivering these pharmacy services. These have been reported back to the International Olympic Committee to ensure continued development and improvement of pharmacy services at future Games.